Optimising ski performance: A multi-scale analysis of ski-snow friction in cold conditions - Kalliorinne, K.; Larsson, R.; Almqvist, A. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Minimising ski-snow friction is essential for optimising performance in winter sports, especially under cold conditions, where resistive forces can significantly affect race outcomes. This study investigates how macro- and micro-scale parameters influence ski friction, offering new insights into ski design.